Electromagnetic navigation bronchoscopy-guided radiofrequency identification marking in wedge resection for fluoroscopically invisible small lung lesions. (6th January 2023) - Yutaka, Yojiro; Sato, Toshihiko; Hidaka, Yu; Kato, Takao; Kayawake, Hidenao; Tanaka, Satona; Yamada, Yoshito; Ohsumi, Akihiro; Nakajima, Daisuke; Hamaji, Masatsugu; Menju, Toshi; Date, Hiroshi
Abstract: OBJECTIVES: We developed a novel wireless localization technique after electromagnetic navigation bronchoscopy-guided radiofrequency identification marker placement for fluoroscopically invisible small lung lesions. We conducted an observational study to investigate the feasibility of this technique and retrospectively compared 2 marking approaches with or without cone-beam computed tomography (CBCT). METHODS: Consecutive patients from January 2021 to March 2022 in our institution were enrolled. Markers were placed central to the lesions either in a bronchoscopic suite under intravenous anaesthesia or a hybrid operation theatre with CBCT under general anaesthesia. The efficacy of the 2 marking methods was compared using an inverse probability of treatment weighting adjusted analysis. RESULTS: Totally 80 markers were placed (45 under CBCT and 35 under fluoroscopy) for 74 patients with 80 lesions [mean size: 6.9 mm (interquartile range: 5.1–8.4) at a median depth from the pleura of 14.0 mm (interquartile range: 8.5–19.5)]. The median distance from marker to lesion was 9.1 mm, with a pleural depth of 15.5 mm. The tumour resection rate was 97.5% (78/80) with the median surgical margin of 10.0 mm (interquartile range: 8.0–11.0). Although the bronchoscopy time was longer using CBCT because of the need for 2.8 scans per lesion, the distance from the marker to the lesion was shorter for marking using CBCT than marking using fluoroscopy (adjusted difference: −4.56, 95% confidence interval: −6.51 to −2.61, P  < 0.001). CONCLUSIONS: Electromagnetic navigation bronchoscopy-guided radiofrequency identification marking provided a high tumour resection rate with sufficient surgical margins. Abstract : The worldwide spread of computed tomography (CT) lung cancer screening has increased the number of newly detected small cancers in recent years [1].